2014
DOI: 10.1007/s10339-014-0604-6
|View full text |Cite
|
Sign up to set email alerts
|

Moving stimuli guide retrieval and (in)validation of coordination simulations

Abstract: According to theories of embodied cognition, visual stimuli can either facilitate or impede the retrieval of language meaning as multimodal perceptual simulations. Here, we introduced a novel experimental paradigm to test the hypothesis that moving stimuli (i.e., motion-defined objects) facilitate coordination comprehension. Participants read coordination descriptions and saw two colored lines that matched the descriptions. Two figures then selected the lines either by moving jointly along them or by standing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…The present paper builds on previous findings [ 5 ] suggesting that a general mechanism of information processing, namely parsing (aka ‘chunking’) shapes reasoning with conjunctions and disjunctions. While there is ample experimental evidence that incoming information is often chunked into smaller units to facilitate processing [ 11 12 ] the nature and properties of these chunks are largely unknown.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The present paper builds on previous findings [ 5 ] suggesting that a general mechanism of information processing, namely parsing (aka ‘chunking’) shapes reasoning with conjunctions and disjunctions. While there is ample experimental evidence that incoming information is often chunked into smaller units to facilitate processing [ 11 12 ] the nature and properties of these chunks are largely unknown.…”
Section: Introductionsupporting
confidence: 67%
“…Nevertheless, experimental evidence increasingly suggests that naive reasoners forego formal rules and instead draw on general cognitive mechanisms when processing complex information. Accordingly, their responses are often modulated by stimuli perceptual properties [ 5 ], by metaphors that ground incoming information onto basic action patterns [ 6 – 7 ], or by mental models that represent, in analogical form, key elements in a message and the relationships between them [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), language (Gallese, 2008 ; Myachykov and Tomlin, 2008 ; Myachykov et al, 2012 ; Lam et al . ; Shaw and Bortfeld ), embodied reasoning (Dumitru, 2014 ), sensory awareness ( Cox and Hong ), numerical cognition ( Dumitru and Joergensen ), auditory perception ( Brogaard and Gatzia ), and time perception ( Homma and Ashida ).…”
mentioning
confidence: 99%
“…As expected, their attention shifted faster between two object parts (in this case, two representations belonging to the same Gestalt) than between two objects (two representations belonging to different Gestalts). Subsequent work by Dumitru (2014) confirmed that Gestalts generate perceptual compatibility effects such that visual groupings of a particular set of stimuli (e.g., two different-coloured lines) had complementary effects on validation scores for conjunction descriptions as opposed to disjunction descriptions. Importantly, language users need not be aware of the dynamics of the concept-grounding process (i.e., why they shift their gaze between stimuli at a certain speed), and there are no language-related constraints that might explain these differences in behaviour.…”
Section: Gestaltmentioning
confidence: 93%